Intestinal malignancy masquerading as primary ovarian carcinoma - Asnani, Mona; Srivastava, Kumkum; Inam, Lubna; Kunwar, Shipra; Singh, Shivani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
About 4-5 % of ovarian tumours are metastatic from other organs, most frequently from the female genital tract, the breast, or the gastrointestinal tract. Ovarian metastases constitute 76% of genital tract metastases from extragenital primary tumours, of which 78% arise in the gastrointestinal tract. Metastatic ovarian tumours, often mistaken as primary ovarian carcinomas. A 37 year old P2+0 presented with c/o - Abdominal distension since last 6 months. It was associated with anorexia, constipation and generalised weakness. Not having any menstrual complaint. P/A: moderate ascitis was there. A mass of 8x10 cm felt through right fornix extending up to right iliac fossa. Mass was firm in consistency with restricted mobility. Uterus felt separately from the mass. Left fornix clear. A right sided ovarian mass of approx. 10x15 cm of variegated consistency identified. Bladder wall was thickened. Small nodules of approximately 1 cm present over dome of bladder under visceral peritoneum. Omentum, ascending colon, transverse colon, descending colon, caecum, greater curvature and lesser curvature were thickened. Liver and spleen were normal. Total abdominal hysterectomy with bilateral Salpingo oophorectomy with partial omentectomy was done. Histopathology Revealed metastatic adenocarcinoma of the genital tract and B/L ovaries. So it was concluded that secondaries from intestinal malignancy can present as primary ovarian malignancy.